A step closer in the management of uncontrolled neuropathic pain: gabapentin-nortriptyline combination - Maladkar, Manish Nilkanth; Tekchandani, Chitra Mohan; Bajaj, Raveena Kanyalal (International Journal of Research in Orthopaedics, 2020)
Neuropathic pain is extremely distressing as it significantly hampers the performance of daily activities and impedes overall quality of life. A large number of illnesses are linked with neuropathic pain like radiculopathy, sciatica, diabetes, herpes infection, spinal injury, stroke, etc. Treating neuropathic pain is challenging as response to the treatment is at times uncertain and associated with undesirable side effects. Uncontrolled neuropathic pain is observed in large group of patients receiving current treatment regimen. Almost half of the neuropathic pain patients need more than two drugs for pain relief. Various clinical trials have demonstrated better efficacy of combination therapy in reducing pain than monotherapy. Utilizing drug combination with different mechanism of action or acting on two different sites has demonstrated superior analgesic effect in painful neuropathic condition. The first tier agents recommended by various guidelines are calcium channel alpha-2-delta ligands and tricyclic antidepressants that act on different pain pathways. A clinical trial has shown enhanced pain relief with no increase in side effects with the administration of gabapentin and nortriptyline combination in patients suffering from neuropathic pain. Moreover, symptoms associated with neuropathic pain like sleep disturbances, altered mood, decreased walking ability, depression and quality of life were also significantly improved. Hence, combination therapy of gabapentin and nortriptyline offers a pivotal modality in the management of uncontrolled neuropathic pain.